2022
DOI: 10.1075/jpcl.00085.han
|View full text |Cite
|
Sign up to set email alerts
|

Context matters

Abstract: This paper presents the results of two largely parallel verbal guise studies that elicited students’ attitudes toward different standard varieties of English. The studies were conducted in the small anglophone Caribbean island country of Grenada. The two studies were contextualized in the domains of education and newscasting, respectively, with the aim of finding out how language attitudes are influenced by context in societies where different endo- and exonormative standards are of relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Moreover, in as far as teachers were, at least historically, viewed as language experts, modelling standardised English and providing norms of English usage (see Deuber 2009;Devonish and Thomas 2012: 181;Hackert 2016: 88), the decision to set the videos in a simulated classroom environment allows the 67 Language Ideologies influencers to, wittingly or unwittingly, claim an expert identity. However, unlike traditional teachers, who use, or are at least expected to use, standardised Caribbean varieties (see Meer et al 2019;Hänsel et al 2022), TikTok teachers model Creole.…”
Section: Non-linguistic Acts Of Identity In the Lod Videosmentioning
confidence: 99%
“…Moreover, in as far as teachers were, at least historically, viewed as language experts, modelling standardised English and providing norms of English usage (see Deuber 2009;Devonish and Thomas 2012: 181;Hackert 2016: 88), the decision to set the videos in a simulated classroom environment allows the 67 Language Ideologies influencers to, wittingly or unwittingly, claim an expert identity. However, unlike traditional teachers, who use, or are at least expected to use, standardised Caribbean varieties (see Meer et al 2019;Hänsel et al 2022), TikTok teachers model Creole.…”
Section: Non-linguistic Acts Of Identity In the Lod Videosmentioning
confidence: 99%
“…A more rigorous approach to the assessment of student attitudes towards local varieties should be implemented in order to rule out subjectivity from variable construction processes. Recent research suggested that student attitudes change when the evaluated variety is uttered by teachers vs. other professional roles (Hänsel, Westphal, Meer, Deuber, 2022). For this reason, future explicit attitude profiling techniques in SoTL should be more context specific.…”
Section: Conclusion: Current Limitations and Future Perspectivesmentioning
confidence: 99%